Elections and electoral practices in Tucumán-Argentina 1870-1880 - Bravo, María Celia (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The objective of this study is to analyze the institutional normativity and political dynamics of the province of Tucumán (Argentina) during the decade of 1870, in the context of the tensions derived from the conformation of the Argentine State. This study in the ield of political history is centered in the analysis of the electoral practices of clubs and committees in the province of Tucumán and their “condescending” relations with working class sectors, without ignoring the central role achieved by the provincial and national State as producer of electoral normativity, as well as a principal actor in the elections. Another aspect of the work involves exploring the functioning of the clubs and committees and their relation with working class sectors, which were generally veriied from a “top to bottom” perspective, through intermediaries(overseers, judges and campaign managers) in a relationship that political historiography has identiied as passive, and whose principal goal was improving the eficacy of previously constructed networks of patronage. These elements allow anappreciation of the way in which in 1870, the incoporation of the leadership of the province of Tucuman into the national  political order allowed for the coniguration of a dynamic of institutional stability, founded on respect for constitutional norms that constituted the system´s main source of legitimacy.